Reliability and validity of the NeuroCognitive Performance Test, a web-based neuropsychological assessment - Morrison, Glenn E.; Simone, Christa M.; Ng, Nicole F.; Hardy, Joseph L. (Frontiers in Psychology, 2015)
The NeuroCognitive Performance Test (NCPT) is a brief, repeatable, web-based cognitive assessment platform that measures performance across several cognitive domains. The NCPT platform is modular and includes 18 subtests that can be arranged into customized batteries. Here we present normative data from a sample of 130,140 healthy volunteers for an NCPT battery consisting of 8 subtests. Participants took the NCPT remotely and without supervision. Factor structure and effects of age, education, and gender were evaluated with this normative dataset. Test-retest reliability was evaluated in a subset of participants who took the battery again an average of 78.8 days later. The eight NCPT subtests group into 4 putative cognitive domains, have adequate to good test-retest reliability, and are sensitive to expected age- and education-related cognitive effects. Concurrent validity to standard neuropsychological tests was demonstrated in 73 healthy volunteers. In an exploratory analysis the NCPT battery could differentiate those who self-reported Mild Cognitive Impairment or Alzheimer’s disease from matched healthy controls. Overall these results demonstrate the reliability and validity of the NCPT battery as a measure of cognitive performance and support the feasibility of web-based, unsupervised testing, with potential utility in clinical and research settings.